THE ROLE OF SECURITY BUREAUCRACY AT THE INTERSECTION OF NATIONAL SECURITY AND ECONOMIC SECURITY (Third Sector Social Economic Review, 2025)
Economic security is essential for a state’s ability to safeguard its national interests and economic values against internal and external threats. This study explores the interplay between economic security and national security strategies, focusing on the role of the security bureaucracy. It examines key aspects such as economic independence, critical infrastructure protection, energy security, and cybersecurity. Using content analysis, the research analyzes official strategy documents from the United States, China, and the European Union, along with discussions in academic literature. The study highlights similarities and differences in the economic security strategies of countries with distinct political systems, showcasing how policymakers address economic security challenges. The findings reveal that economic security is a core component of national security, with the security bureaucracy’s effectiveness being crucial in enhancing international competitiveness. Moreover, the research emphasizes the interconnectedness of economic security with military expenditures, diplomacy, and intelligence, advocating for a comprehensive approach to security. It underscores the importance of integrating economic security policies with sustainable development and societal welfare goals. Effective coordination of the security bureaucracy is identified as a vital factor in implementing successful national security strategies, ensuring resilience against emerging threats.
Keywords: Economic Security; National Security Strategies; Security Bureaucracy; Critical Infrastructures; National Interests.